The militarization of public celebrations in Bourbon and Independent Chile - Valenzuela Márquez, Jaime (Revista Complutense de Historia de América, 2012)
This article examines the increasing deployment of army and military symbols and practices in eighteenth- century Chile. It then traces the evolution of this process during the period of independence from Spain, by focusing on the increasing military activity of the early nineteenth century, and the transformations experienced by the political administration and their symbolic liturgical practices under the nation.